Effect of activator spraying amount on the thickness and appearance of water transfer printing film coating results - Gilang Supanto; Ahmad Roziqin; Febrian Arif Budiman (Universitas Negeri Semarang, 2026)
This research investigates the influence of activator spray quantity on the thickness and visual appearance of Water Transfer Printing (WTP) film coatings on Aluminium alloy 5052 surfaces. The study employed an experimental method, varying activator spray quantities at 2, 3, 4, and 5 times. Coating thickness was measured using a Coating Thickness Tester, while appearance was visually assessed by 10 experts based on surface cleanliness, substrate coverage, and pattern neatness. The results indicate a positive influence of activator spray quantity on both parameters. For coating thickness, increasing activator quantity consistently led to greater average film thickness, with a total increase of 63.06% from 2 to 5 sprays (averaging 17.81% per additional spray). Concurrently, the visual appearance improved across all criteria; surface cleanliness increased by an average of 32.62%, substrate coverage by 29.56%, and pattern neatness by 31.79% for each additional spray. The most drastic improvements in both thickness and appearance criteria were generally observed in the transition from lower to intermediate spray quantities, suggesting an optimal activator range for great WTP results.